The Role of the Natural Resource Curse in Preventing Development in Politically Unstable Countries: Case Studies of Angola and Bolivia - Saraly Andrade; Joaquin Morales (Institute for Advanced Development Studies (INESAD), 2007)
For about three decades now, development economics researchers have consistently claimed that third world resource-rich countries were not developing as well and/or as fast as they were expected to, given that their natural resources endowment was considered a great opportunity for development. The phenomenon of underperformances concerning primary commodity exporters relative to non resource-rich countries has been often referred to as to the Natural Resource Curse . The authors use an historical and political approach to the manifestations of the curse in the specific cases of Angola and Bolivia, both resource abundant countries, but suffering among the lowest development standards in their respective continents. In chapter one, the authors make a quick review of the literature explaining both causes and manifestations of the Resource Curse. The authors go beyond the classical Dutch Disease explanations and show how natural resources lead to behaviours of looting, rent-seeking and civil confrontations. In chapter two, the authors present the framework where they adjust the African Anti-growth Policy Syndromes described by Paul Collier to the specific case of the Natural Resource curse. In addition, they add some considerations of the negative effect of natural resource extraction by analysing externalities on environment, education and inequalities. Chapters three and four analyse the case studies of Angola and Bolivia respectively, emphasizing the role of historical context explaining policy behaviour and the critical impact of unexpected windfalls and sudden price collapses. The authors find that natural resources could sustain long lasting conflicts, but that conditions of fractionalization of society determine the possibility of conflict. A country divided in two rigid political factions is more prone to internal conflict, like in Angola, whether in countries where frontiers between blocks are blurried or the country is multi-polar, like in Bolivia, the risks of long-lasting civil war seem less important. Apart from conflict, the authors show that lack of institutions and inequality make of natural resources a source of political instability that has far more impact on economic performances than other factors.
Keywords: N2; N5; O1; 330; Natural Resource curse; Rent-seeking; Civil War; Angola; Bolivia